T-Test for visualizing frequently used Arabic words - Yusof, R.J.R.; Zainuddin, R.; Baba, M.S.; Yusoff, Z.M. (2009)
The aim of visualizing the frequently used words is to solve the problem of reading comprehension. This is referring to the case of the non-Arabic speakers of the Muslim community, reading or reciting extensively an Arabic document (the Quran) without comprehension. This study outline an experiment testing whether there is any significant difference on the level of comprehension when images are used as part of the reading material of the Arabic text. It was found that using text only translation, resulted in no significant difference of the level of comprehension and the expected values. However, there is significant difference on the level of comprehension between Arabic text translation of the frequently used words and the text image of the frequently used word. Â© 2009 Asian Network for Scientific Information.